A novel technique for bone marrow concentrate aspiration from the intercondylar notch during arthroscopic ACL reconstruction. Issue 12 (31st December 2018) - Figueroa, David; Bernal, Nazira; Arellano, Sergio; Donoso, Rodrigo; Figueroa, Francisco; Vaisman, Alex; Calvo, Rafael
Objectives: Anterior cruciate ligament Reconstruction (ACL-R) is a frequent surgery with a failure rate of 8-10%, being a cause the lack of integration of the graft. Methods of biological augmentation have been developed, such as the extraction of human mesenchymal cells by aspiration of BMC. Objective: describe and demonstrate the safety of a new arthroscopic technique of BMC aspiration from the femoral intercondylar notch. Methods: Prospective non-randomized clinical study of 45 consecutive patients undergoing anatomic ACL-R with hamstring autograft. Patients with Multiligamentary injuries or revision ACL surgery were excluded. Control group was composed by 19 patients that underwent isolated ACL-R. Intervention group was composed by 29 patients who underwent ACL-R, BMC aspiration and subsequent instillation of the BMC. Variables assessed to compare both groups were: Demographics, Surgical Time and Complications (hemarthrosis, rate of infection and risk of fracture). BMC Aspiration Technique was performed before tunnel drilling and shutting-off the water pump. Through the medial portal, the 14-gauge trocar/needle aspiration device was introduced and positioned into the upper and central region of the intercondylar notch. With a clockwise-like twisting motion, the trocar was used to pierce the cortex 25 mm into the distal femur, obtaining 60 ml of BM which was processed with the Angel system (ArthrexR). Finally, under dry arthroscopic vision, the BMC was instilled in both bone tunnels and into the graft. Statistical analysis was performed in stata 11, considering a statistical significance of 5%. Results: No demographic differences were reported. The surgical time of the control group was 50.57 min (SD 8.44) and intervention group 65.69 min (SD 10.98) (p <0.011). 0% of complications associated with the procedure were reported. Conclusion: The aspiration of BMC through the femoral intercondylar notch during the arthroscopic ACL-R, is a safe, reproducible technique without associated complications, however, it significantly increases the surgical time.